Tacit knowledge manifestations in an institute of higher learning - Haron, Haryani; Alias, Rose Alinda (2006)

(untitled)
Organizational knowledge, the most important resource in an organization, constitutes of many types of knowledge. The objective of the study is to understand the nature of organizational tacit knowledge, focusing on its manifestations in an institute of higher learning. This paper viewed organizational knowledge in taxonomy of the diffusion of knowledge and the degree of tacit ness. Both dimensions are viewed along a continuum. A conceptual organizational tacit knowledge framework is used in collecting the data for this study. Data are collected through interviews with scholars in an academic institution. This study uses the if-then-because methodology in analyzing the data. A total of twenty one items, served as indicators of tacit knowledge is identified. Seven categorizations of tacit knowledge manifestations in an institute of higher learning are extracted from the indicators collection.